Asystole Detected by Implantable Loop Recorders: True or False? - Ali, Hussam (Ann Noninvasive Electrocardiol, 2014)
We report a case of a false asystole detected by an implantable loop recorder a few days after its implantation. In the discussion section we try to give some hints to help cardiac electrophysiologists in distinguish true from false asystoles, in order to avoid unuseful and potentially dangerous implantations of pacemakers.